2016
DOI: 10.15376/biores.11.4.9710-9722
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Eucalyptus Powder with Alkaline Ionic Liquid [Mmim]DMP under Microwave Conditions

Abstract: An orthogonal design was used to study three factors-melting temperature, time, and solid-liquid ratio-and how they affected the dissolution rate of eucalyptus powder. The optimum solution conditions were 170 °C, 20 min, and a solid-liquid ratio of 1:25. Composition analysis of the residue indicated that, in the dissolving process, acidinsoluble lignin was converted into acid-soluble lignin, and a part of the lignin was degraded or modified. After dissolution, the crystalline structure of cellulose deteriorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Other process parameters such as stirring speed, solid/liquid ratio, wood and cellulose particle and molecular size [60,95,96], the use of microwave heating [97,98], and ultrasonication [99] are also important and have been thoroughly explored in the literature. It has also been observed that wood dissolution is affected by environmental conditions.…”
Section: Impact Of Dissolution Conditionsmentioning
confidence: 99%
“…Other process parameters such as stirring speed, solid/liquid ratio, wood and cellulose particle and molecular size [60,95,96], the use of microwave heating [97,98], and ultrasonication [99] are also important and have been thoroughly explored in the literature. It has also been observed that wood dissolution is affected by environmental conditions.…”
Section: Impact Of Dissolution Conditionsmentioning
confidence: 99%
“…More importantly, ionic liquids also have amphipathic properties which allows easy precipitation of dissolved lignin to form lignin micro/nano-particles by adding acid water (Acid deionized water). In this paper, 1,3-dimethyl-imidazolium dimethyl phosphate ([Mmim][DMP]), which is known to have a good lignin solubility according to the researches by our team [10,11] , was employed to develop a rapid and complete alkali lignin dissolution method with low temperature and characterize the regenerated lignin micro/nano-particles by Fourier transform infrared spectroscopy (FT-IR), the elemental analysis, gel permeation chromatography (GPC), thermogravimetric analysis (TGA), 2D heteronuclear single quantum coherence nuclear magnetic resonance (2D HSQC NMR) spectroscopy. Furthermore characterization of regenerated lignin micro/nano-particles morphology was observed by scanning electron microscopy (SEM) and polarized light microscopy (PLM).…”
Section: Introductionmentioning
confidence: 99%